Analisis Kualitatif Technostress pada Guru dalam Penggunaan Teknologi Informasi di Masa Pandemi Covid-19 - Ramdaning Puri Pradani; Diah Priharsari; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Technostress is a negative effect that occurs on attitudes, human behavior, ways of thinking, and mentality due to the use of unhealthy information technology, either directly or indirectly. The negative impact of this technology is found in various sectors, most notably education. Teachers in the education sector face technostress as a result of unhealthy information technology use, which intensifies during the Covid-19 pandemic. The intensity of information technology use has been increasing during the Covid-19 pandemic, compared to before the pandemic situation, as teaching activities, meetings and completing school assignments are conducted from home or online. If the teachers continue to experience technostress, their performances will suffer, and they will be unable to complete the task properly. The purpose of this study is to identify the factors that contribute to teachers experiencing technostress, the impact that technostress has on teachers and ways to alleviate technostress both in teachers as an individual and organizational support in schools. This is a qualitative study conducted through the use of case studies. The case study subjects in this study consisted of ten teachers and technicians from SMK Negeri 1 Nganjuk. The interview method was used to collect data, and thematic analysis was used to analyze the data. The findings of this study indicate that teachers are subjected to four types of technostress, namely techno-complexity, techno-overload, techno-invasion and techno-uncertainty. The impact of the Covid-19 pandemic on teachers who use information technology is both negative and positive. Additionally, this study discusses how to overcome technostress; there are three ways in which individuals can reduce technostress, namely self-efficacy, mindfulness, and internal motivation. Meanwhile, three types of organizational support aim to overcome technostress, including technical support providers, literacy facilities and engagement facilities.